2015
DOI: 10.1128/aem.00650-15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abiotic and Biotic Stresses on the Internalization and Dissemination of Human Norovirus Surrogates in Growing Romaine Lettuce

Abstract: Human norovirus (NoV) is the major causative agent of fresh-produce-related outbreaks of gastroenteritis; however, the ecology and persistence of human NoV in produce systems are poorly understood. In this study, the effects of abiotic and biotic stresses on the internalization and dissemination of two human NoV surrogates (murine norovirus 1 [MNV-1] and Tulane virus [TV]) in romaine lettuce were determined. To induce abiotic stress, romaine lettuce was grown under drought and flood conditions that mimic extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 69 publications
(95 reference statements)
1
19
0
Order By: Relevance
“…The 14-day study period was chosen because by 7 and 14 days plants can be harvested and because of the importance of the period between a contamination event and harvest time. In addition, the 14-day study period used in our study is similar to or longer than the study periods reported for studies dealing with the survival of HuNoV (7 days) or TV and MNV (14 days) on leaf surfaces (45,46). Collectively, because HuNoV RNA showed a higher degree of stability than MNV, SaV, and TV RNAs and RNA titers correlated significantly with infectivity titers for all surrogates, our results suggest that infectious HuNoVs contaminating leafy greens close to the harvest time may persist until the vegetables are harvested.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…The 14-day study period was chosen because by 7 and 14 days plants can be harvested and because of the importance of the period between a contamination event and harvest time. In addition, the 14-day study period used in our study is similar to or longer than the study periods reported for studies dealing with the survival of HuNoV (7 days) or TV and MNV (14 days) on leaf surfaces (45,46). Collectively, because HuNoV RNA showed a higher degree of stability than MNV, SaV, and TV RNAs and RNA titers correlated significantly with infectivity titers for all surrogates, our results suggest that infectious HuNoVs contaminating leafy greens close to the harvest time may persist until the vegetables are harvested.…”
Section: Discussionmentioning
confidence: 75%
“…A previous study, however, implemented an extreme weather situation where drought or flooding was applied for 14 days (45). That study showed a negative effect of drought on virus internalization.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Viruses, including norovirus and rotavirus, cause foodborne outbreaks, especially due to their persistence in the environment and their low infectious doses (10 to 100 particles) (7,8). Murine norovirus, Tulane virus, and sapovirus have been found to attach to the surface of or within the tissues of romaine lettuce and strawberries (9)(10)(11)(12)(13), which suggests that preharvest viral contamination is a public health concern. To reduce the incidence of viral foodborne illnesses caused by contaminated produce, it is essential to understand the environmental and agricultural factors that control the stability and, therefore, the infectivity of foodborne viruses.…”
mentioning
confidence: 99%